The presence of an exceedingly large thymoma in a 6-year-old patient - Małgorzata Stopa; Zuzanna Piątek; Łukasz Moskal; Katarzyna Wijatkowska; Wojciech Kustrzycki; Romuald Cichoń (Termedia Publishing House, 2022)
Kardiochirugia i Torakochirurgia Polska 2022; 19 (1): 47-48